Effects of government assistance programs on the well-being of urban low-income households during COVID-19 pandemic in Malaysia - Zaidi, Mohd Azlan Shah; Shukor, Md Shafiin; Kefeli, Zurina; Haron, Aainaa Amirah; Sudin, Ros Amira Mohd (Asian Development Policy Review, 2024)
This study aims to investigate the effects of government assistance programs on the well-being of urban low-income households during the COVID-19 pandemic in Malaysia. The COVID-19 pandemic has had a significant impact on Malaysians’ well-being, affecting a variety of factors such as income, health, and standard of living. To address the repercussions of the pandemic, the government has implemented diverse economic stimulus packages. Household well-being is assessed using four indicators: income, health, cost of living, and social relations. A cross-sectional survey was conducted in six regions of Malaysia. Data from 706 respondents was analysed using the Structural Equation Modelling (SEM). The main findings reveal that government assistance programs enhance household well-being by reducing the cost of living, increasing income, improving health, and fostering social interactions. Specifically, among the four focused aspects, the programs have the most significant impact on improving the health of low-income households. These programs have the least effect on enhancing well-being through the reduction of the cost of living. Consequently, these findings provide valuable information to policymakers in understanding the effectiveness of government assistance programs during the crisis period. This nationwide evidence-based analysis will contribute additional insights to the formulation of future assistance programs aimed at improving the well-being of low-income households.